MEDICINAL PLANTS IN MEDIEVAL TREATISES: MEDICINAL PROPERTIES, APPLICATION, DESCRIPTION (Journal of Oriental Studies, 2024)
Traditional medicine is understood as a set of therapeutic and hygienic measures practiced in local human populations. This knowledge is based on the experience of one or a number of generations of people and was transmitted orally and later in written works.  Each period had its own healing art and it is clearly recorded in the written heritage of the healing healers of that period. Ancient medical treatises, written primarily on the basis of personal observations and borrowed materials, are sometimes difficult to understand due to significant differences in the concepts and terms of traditional and modern scientific medicine and require in-depth analysis. The analysis of medical treatises is a serious scientific task that requires the joint efforts of several specialists; doctors, botanists, ethnographers, linguists and pharmacy specialists.The article presents a list of herbs that were often taken in Turkic folk medicine in ancient times and are still used today in the treatment of various ailments, as well as the main properties of these medicinal plants described in written works. The sources of research in the article are the medical treatises “Dastûr al-'ilāj” (early 16th century) and “Asrār al-Аtibbā’” (anonymous), which discuss the features of the medical traditions of the Turkic peoples in the Middle Ages.Keywords: medieval treatise, "Dastûr al-'ilāj", "Asrār al-Аtibbā’", medicinal herbs.